Biofabrication of zinc oxide nanoparticles using Moringa oleifera, characterization and statistical optimization for their application in crystal violet adsorption - Meshayil M. Alsolmi; Noura El-Ahmady El-Naggar; Mashael I. Alqurashi; Ragaa A. Hamouda (Scientific Reports)
Abstract Crystal violet (Cry) is an essential textile dye belonging to the triphenylmethane group, that is widely used in the textile industry. It is also applied for paper printing and Gram staining. Previously, it was significant as a topical antiseptic due to its antibacterial, antifungal, and anthelmintic properties. Despite its various applications, crystal violet has been recognized as a biohazard dye due to its toxic and carcinogenic properties. It persists in the environment with long-lasting effects and has detrimental impacts. In this research, water extract from Moringa oleifera leaves is employed as environmentally friendly methods to synthesize zinc oxide nanoparticles (Mo/ZnO-NPs), and characterized by TEM, EDX, FT-IR, and Zeta potential. Mo/ZnO-NPs exhibit a Zeta potential of − 21.9 mV, and X-ray diffraction (XRD) analysis confirms their crystallographic structure. The size of the biogenic Mo/ZnO-NPs ranges from 5.52 to 41.59 nm. This study was designed to estimate and maximize the ability of Mo/ZnO-NPs to remove crystal violet using Central Composite Design (CCD), considering pH (ranging from 3 to 11), incubation time (ranging from 30 to 150), nanoparticles concentrations (ranging from 0.2 to 1.8 mg/mL), and crystal violet concentrations (ranging from 25 to 125 ppm). The maximum percentage value of removal of crystal violet by Mo/ZnO-NPs was 97.26 with optimal conditions of pH 9, incubation time 120 min, Mo/ZnO-NPs 1.4 mg/mL, and crystal violet concentration of 50 ppm. The best-predicted conditions that caused the highest removal of crystal violet (97.8%) were determined using the desirability function as pH 10, incubation time of 140 min, Mo/ZnO-NPs concentrations of 1.3 mg/mL, and a concentration of crystal violet of 80 ppm. Under these optimal conditions, the maximum experimental crystal violet removal% by Mo/ZnO-NPs was (98.7%) was verified. Mo/ZnO-NPs synthesized by Moringa oleifera can be a promising candidate for the adsorption of crystal violet.